Autologous and allogeneic stem-cell transplantation for transformed chronic lymphocytic leukemia (Richter's syndrome): a retrospective analysis from the chronic lymphocytic leukemia subcommittee of the Chronic Leukemia Working Party and Lymphoma Working Party of the European Group for Blood and Marrow Transplantation - Cwynarski, Kate; Dreger, Peter (Journal of clinical oncology, 2012)
Purpose Patients with Richter’s syndrome (RS) have a poor prognosis with conventional chemotherapy. The aim of this study was to evaluate the outcome after autologous stem-cell transplantation (autoSCT) or allogeneic stem-cell transplantation (alloSCT) in RS. Patients and Methods A survey was sent to all European Group for Blood and Marrow Transplantation centers assessing transplantations performed for RS. Eligibility criteria included a diagnosis of RS or secondary lymphoma before SCT, age Ն 18 years, and SCT performed from 1997 to 2007. Data were analyzed by descriptive statistics and methods from survival analysis.Results Fifty-nine patients were registered. Thirty-four patients had received autoSCT, mostly because of chemotherapy-sensitive disease, and 25 had received alloSCT, with 36% being refractory to chemotherapy at SCT. In 18 allograft recipients (72%), reduced-intensity conditioning (RIC) was used. Three-year estimates of the probabilities of overall survival and relapse-free survival (RFS) and the cumulative incidences of relapse and nonrelapse mortality were 36%, 27%, 47%, and 26% for alloSCT and 59%, 45%, 43%, and 12% for autoSCT, respectively. Taking into account the limitations set by the low number of events and age younger than 60 years, chemotherapysensitive disease and RIC were found to be associated with superior RFS after alloSCT in multivariate analysis. Factors with a signiﬁcant impact on autoSCT could not be identiﬁed.Conclusion Patients with RS who are sensitive to induction chemotherapy appear to beneﬁt from consolidation with transplantation strategies, and prolonged survival was observed in a proportion of patients.